Challenges in using interaction data for trace link creation - Hübner, Paul; Paech, Barbara (Softwaretechnik-Trends, 2018)
For direct usage of trace links during a development project the precision of information retrieval (IR) based trace link creation is not sufficient. Too many false links generated by IR hinder developers to directly use the resulting links and require further assessment by an expert. Thus, we develop an interaction based trace link creation approach (IL) aiming to create trace links with perfect precision. In IL we utilize the interactions of developers recorded in the IDE while working on a requirement.
Workshop des Arbeitskreises "Traceability/Evolution" (FG-ARC)
Der Artikel hat keine eigene Titelseite, daher wird die übergeordnete URL verwendet
Gesehen am 05.02.2020